Efecto del estiércol y la fertilización NAK en la acumulación de materia seca en hofdeum vulgare l. var. zapata en un suelo acido en Trujillo – La Libertad - Mestanza Sáenz, Katherine Julissa (2013)
In the present work it was evaluated the dung. s effect and the fertilization NPK in the dry-matter accumulation in Hordeum vulgar e L V ar. Zapata in an acid ground of the high plateau in an experiment in flowerpots, which installed the January 25 the 2012 in experimental tables adjacent to the Suelos' s Laboratorio of Ciencias Agropecuarias's Faculty, once was located in Trujillo's University Nacional, using a design complete blocks at random with four repetitions. Each experimental unit was shaped for a flowerpot with two kilograms of ground with pH 4.4 and 1.2cmol(+) kilograms ground-1 of changeable acidity once 3990 msnm was located in the provinces of Chuco's Santiago. The treatments were three dung sources: ovme, bovine and the mixture of avine and bovine (50%+50%) incorporated to the planting at the rate of 4grams.bag-1 and for four fertilization levels NPK: 0-0-0; 30-30-30; 60 60-60 y 90-90-90 ground mg/kg of N, P205 y K20, respectively. He evaluated the dry-matter grains, foliage, aerial (grains+foliage), radicular, total, number of macollas and height from the beginning. Dry-rnatter accumulation of grains with dung found the principal itself of avine to 90-90-90·s dose. The principal dry-matter accumulation of foliage, dry matter aerial, dry matter total and macollos's number with dung ofbovine to the dose of 60-60-60 and with the dungs mixture of avine and bovine (50%+50%) to 90-90-90 ·s dose.With dung of avine and the control treatment is obtained the minar accumulation of dry matter radicular, and, the treatments under consideration they did not affect height from the beginning.